Exposure-enhanced cognitive behavioral therapy for adolescents with binge eating: An initial case series. (October 2021) - Manasse, Stephanie M; Lampe, Elizabeth W; Abber, Sophie R; Butler, Rachel; Gillikin, Lindsay; Trainor, Claire
Binge eating (BE) often develops during adolescence and is associated with deleterious psychological and physical consequences. Current treatments for adolescents achieve suboptimal results, likely due to failure to adequately address fear of weight gain (FOWG) which maintains BE. Thus, exposure treatment (the most powerful intervention for fear) may be a promising approach. However, exposure treatment has only minimally tested in adults with BE and never tested in adolescents. Thus, the current study is the first to evaluate a 4-session exposure module within a 12-session standard cognitive behavioral therapy for adolescents with BE. We recruited adolescents with BE ( N = 5) and examined treatment feasibility, acceptability, and preliminary effects on FOWG and eating pathology. Overall, the 4-session exposure module was feasible and acceptable and showed preliminary evidence that it could reduce FOWG. However, several participants did not endorse significant fears of weight gain; rather, these participants reported that fears of deprivation or social judgment were more related to their BE. Future research should test higher doses of exposure and further examine the role of fear of deprivation/social judgment. Finally, future iterations of this treatment could include more parent involvement or test exposure in combination with treatments other than cognitive behavioral therapy, such as family-based treatment.